Personality traits, difficulties in emotion regulation and academic satisfaction in a sample of argentine college students - Trógolo, Mario Alberto (2012)
In recent years academic satisfaction in college students has been subject of considerable research, analysis and theorizing among educational researchers. The purpose of the current study was to examine the contributions of personality traits, using the Big Five Factor Model, and difficulties in emotion regulation to predict academic satisfaction in a sample of university students in Cordoba, Argentina. Contrary to expectations, results of hierarchical regression analysis showed that neither the Big Five traits nor difficulties in emotion regulation made a significantly contribution to the prediction of academic satisfaction. However when considering the overall profile of personality and emotion regulation, two subgroups theoretically and empirically consistent with significant differences in academic satisfaction were identified. Results, implications and limitations of the current study are discussed.